2004
DOI: 10.1103/physrevlett.93.176604
|View full text |Cite
|
Sign up to set email alerts
|

Current-Induced Excitations in Single Cobalt Ferromagnetic Layer Nanopillars

Abstract: Current-induced magnetic excitations in Cu/Co/Cu single layer nanopillars (∼50 nm in diameter) have been studied experimentally as a function of Co layer thickness at low temperatures for large applied fields perpendicular to the layers. For asymmetric junctions current induced excitations are observed at high current densities for only one polarity of the current and are absent at the same current densities in symmetric junctions. These observations confirm recent predictions of spintransfer torque induced sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
76
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 14 publications
13
76
1
Order By: Relevance
“…The former are in good agreement with previous theoretical [27,39] and experimental studies [36]. They provide an improved understanding of the coupled dynamics between magnetizations and spin transport, and the excitation of spin wave modes for negative lateral spin transfer torques.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The former are in good agreement with previous theoretical [27,39] and experimental studies [36]. They provide an improved understanding of the coupled dynamics between magnetizations and spin transport, and the excitation of spin wave modes for negative lateral spin transfer torques.…”
Section: Discussionsupporting
confidence: 79%
“…[27], several experimental [36][37][38] and theoretical [28,[39][40][41] studies have been performed to understand the lateral spin diffusion effect. Özyilmaz et al [36] experimentally observed current-induced excitation of a single ferromagnetic layer. For an asymmetric Cu/Co/Cu nanopillar structure, current-induced excitations were observed for only one polarity of the current, where, according to the prediction [27], the lateral spin transfer torque should increase the magnetization inhomogeneity.…”
Section: Previous Studies On Non-local Spin Transfer Torque Due To Lamentioning
confidence: 99%
“…Both the threshold currents and the current induced hysteresis in these junctions exhibit a well defined magnetic field dependence. Similar to the high field excitations, 18 the low field single layer switching events lead to a low resistance state. However, the threshold currents and the corresponding changes in device resistance in the two regimes are very distinct.…”
mentioning
confidence: 99%
“…With a few exceptions 17,18 spin transfer devices consist of at least two exchange decoupled ferromagnetic regions, which play distinct roles. One of these regions is designed such that it simultaneously provides both a spin polarized current and acts as a reference layer relative to which the manipulation of the second ferromagnetic region is detected with the giant magnetoresistance effect (GMR).…”
mentioning
confidence: 99%
“…Owing to its non-conservative nature, this spin torque (ST) can act as effective negative magnetic damping and thereby excite magnetization selfoscillations 3,4 . ST oscillators (STO) have been realized in nanoscale spin valves 3,[5][6][7] , point contacts to magnetic multilayers [8][9][10] and nanoscale magnetic tunnel junctions [11][12][13][14][15] . Recently, a new type of STO based on current-induced spin orbit (SO) torques in a Permalloy(Py)/platinum(Pt) bilayer was demonstrated [16][17][18] .…”
mentioning
confidence: 99%